Influence of Intramolecular Charge Transfer and Nuclear Quantum Effects on Intramolecular Hydrogen Bonds in Azopyrimidines - Bártová, Kateřina; Čechová, Lucie; Procházková, Eliška; Socha, Ondřej; Janeba, Zlatko; Dračínský, Martin (The Journal of organic chemistry, 2017)
Intramolecular hydrogen bonds (IMHBs) in 5-azopyrimidines are investigated by NMR spectroscopy and DFT computations that involve nuclear quantum effects. A series of substituted 5-phenylazopyrimidines with one or two hydrogen bond donors able to form IMHBs with the azo group is prepared by azo coupling. The barrier of interconversion between two rotamers of the compounds with two possible IMHBs is determined by variable temperature NMR spectroscopy and it is demonstrated that the barrier is significantly affected by intramolecular charge transfer. Through-hydrogen-bond scalar coupling is investigated in 15N labeled compounds and the stability of the IMHBs is correlated with experimental NMR parameters and rationalized by path integral molecular dynamics simulations that involve nuclear quantum effects. Detailed information on the hydrogen bond geometry upon hydrogen-to-deuterium isotope exchange is obtained from a comparison of experimental and calculated NMR data.